DETECTION OF SOME BACTERIAL CAUSES OF WATERY DIARRHEA IN THE PROVINCE OF BAGHDAD AND SOME NORTHERN GOVERNORATES WITH ASTUDY OF PATHOLOGICAL EFFECTS - Kadhim, Suadad; Saleh, Dhuha (Iraqi Journal of Science, 2024)
The present study Investigate the study on the causes of diarrhea epidemic in the province of Baghdad and some northern governorates since been collected 140 stool samples of water of different ages for the period from the beginning of the month of October 2007 to the end of August 2008, after culture ,microscopic biochemical testing diagnosed (113) bacterial isolates was among them ( 66) isolation rate of (% 47.14) only belonging to Vibrios cholera, Vibrio cholerae are divided by (58) in a rate (% 87.87) and returned to the pattern under serum Inaba, and (5) isolates, a rate (% 7.57) and returned to the pattern under serum Ogawa, all belonging to the pattern of bio-El-Tor and three isolates by (4.54%) belonging to non-cholera vibrios NAG The study showed the presence of 10 bacterial isolates were similar in most characteristics of the cholera bacteria, vibrios with some of the differences that emerged when Biochemical tests, which gave a negative result of the examination and testing of cholera red stitching and nitrate reduction Histopathological study using experimental animals indicate similarity in pathogenesis of V. cholerae and vibrio like bacteria ,both cause congested spleen and liver and desquamation in the intestinal villi